2017
DOI: 10.1080/15384101.2017.1317417
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arterial administration of tumor-targetingSalmonella typhimuriumA1-R regresses a cisplatin-resistant relapsed osteosarcoma in a patient-derived orthotopic xenograft (PDOX) mouse model

Abstract: Previously, a patient-derived orthotopic xenograft (PDOX) model was established with a lung metastasis from an osteosarcoma patient which developed after adjuvant cisplatinum (CDDP) treatment. In this model, we previously demonstrated the efficacy of trabectedin (TRAB) and temozolomide (TEM) compared with CDDP. In the present report, osteosarcoma tissue was implanted orthotopically in the distal femur of mice which were randomized into the following groups when tumor volume reached approximately 100 mm 3 ; On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 41 publications
1
56
0
Order By: Relevance
“…Several models of PDX of osteosarcoma has been described in the literature for various assessment including epigenomic, drug testing and therapeutic development [122][123][124][125][126]. These immunodeficient were very recently used for analysing the tumor-targeting amino-acidauxotrophic strain Salmonella typhimurium A1-R [125,126]. Salmonella typhimurium A1-R exhibit a marked potential for infecting cancer cells and inducing cell death.…”
Section: Lymphocytes Subpopulations In Osteosarcoma and Therapeutic Imentioning
confidence: 99%
See 1 more Smart Citation
“…Several models of PDX of osteosarcoma has been described in the literature for various assessment including epigenomic, drug testing and therapeutic development [122][123][124][125][126]. These immunodeficient were very recently used for analysing the tumor-targeting amino-acidauxotrophic strain Salmonella typhimurium A1-R [125,126]. Salmonella typhimurium A1-R exhibit a marked potential for infecting cancer cells and inducing cell death.…”
Section: Lymphocytes Subpopulations In Osteosarcoma and Therapeutic Imentioning
confidence: 99%
“…Salmonella typhimurium A1-R exhibit a marked potential for infecting cancer cells and inducing cell death. More interestingly, bacteria induced the regression of cisplatin-resistant relapsed tumors [126].…”
Section: Lymphocytes Subpopulations In Osteosarcoma and Therapeutic Imentioning
confidence: 99%
“…In order to achieve this purpose, the patient‐derived orthotopic xenograft (PDOX) mouse models for osteosarcoma has been established in some laboratories . Although the perceived technical complexity and the appropriate quality control needed to optimize the viability of the original human tumor cells, such PDOX models can play an important role for individualized therapy approaches in translational research as they are more closely recapitulate the heterogeneity of primary human osteosarcoma . In our study, we showed suppression of spontaneous metastasis to the lungs with the repeated systemic administrations of rVSV‐K in a syngeneic ectopic murine LM8 osteosarcoma mouse model.…”
Section: Discussionmentioning
confidence: 78%
“…It has been recently observed that a large genomic heterogeneity exists between osteosarcoma patients so that individualized precision therapy is needed in the management of osteosarcoma . In order to achieve this purpose, the patient‐derived orthotopic xenograft (PDOX) mouse models for osteosarcoma has been established in some laboratories . Although the perceived technical complexity and the appropriate quality control needed to optimize the viability of the original human tumor cells, such PDOX models can play an important role for individualized therapy approaches in translational research as they are more closely recapitulate the heterogeneity of primary human osteosarcoma .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PDOX models of sarcoma (47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64), cervical cancer (65-67) as well as melanoma (68)(69)(70)(71)(72)(73)(74) have also been developed.…”
Section: Patient-derived Orthotopic Xenograft (Pdox) Mouse Models Of mentioning
confidence: 99%